Replication Report on Altmann et al. (2022) - Sebastian Bachler; Andrea Erhart; Armando Holzknecht (Institute for Replication (I4R), 2023)
In the paper of, Altmann et al. (2022) the authors investigate whether positive effects which are due to behavioral policy interventions in policytargeted domains come along with negative effects in policy non-targeted domains. Using lab and online experiments where subjects have to solve one policy-focused decision task and one non-focused background task, the authors show that increasing incentives or steering attention to the former led to higher attention spans, lower default adherence rates, and a higher choice quality in the decision task. However, because of steering participants focus to the decision task, lower choice quality and lower attention spans in the background task emerged as a consequence, which was particularly pronounced among individuals with lower cognitive capabilities and complex decision tasks. Essentially, the authors also describe that the negative effects in the background tasks offset the positive effects in the decision task, ultimately yielding a net-zero effect overall. Therefore, the authors emphasize policymakers to also consider the potential negative cognitive spillovers in order to not overestimate the benefits of behavioral policy interventions. All the results the authors in the main text report are significant on 5% and 1% significance levels. All findings presented in the main text of the paper can be replicated using the original Stata code and verified thoroughly using R. Additionally, we performed two robustness tests to ensure the reliability of the paper's main results, and they remained consistent. Hence, the reported findings in the paper appear to be robust.
Keywords: 330